Fototerapia aplicada durante o treinamento e o destreinamento: efeitos no treinamento de força e treinamento aeróbio - Paiva, Paulo Roberto Vicente de (2019)
Regular physical exercise can improve cardiovascular capacity, increase muscle mass and reduce body fat, and for this, two training programs can be employed. Strength training changes predominantly the strength and muscle volume, and in turn, aerobic training interferes predominantly with the cardiovascular fitness and body fat mass. However, the question about the permanence of these alterations after a period without training, called detraining, is not well understood so far. Photobiomodulation therapy (PBMT) has already presented ergogenic effects when combined with a physical training program. Thus, the aim of this study was to investigate the effects of phototherapy on maintaining the gain gained through strength training and aerobic training during the detraining period. For this, two studies were performed separately. In the first study, 48 sedentary men performed a strength training protocol twice a week on nonconsecutive days for 12 weeks. PBMT was applied to the quadriceps muscle before each training session and also to detraining, with a total dose of 180 J in each thigh. In the second study, 60 sedentary men performed aerobic training 3 times a week on nonconsecutive days for 12 weeks. PBMT was applied to the quadriceps, hamstrings and gastrocnemius muscles before and after each training session and also in detraining, with a total dose of 510 J in each lower limb. The detraining period lasted 04 weeks in both studies. In strength training, peak torque was evaluated by the maximal voluntary contraction (MVC) test on isokinetic dynamometer and the maximum force by the one-repetition maximum (1RM) test in the leg press and chair extension exercises. In aerobic training were evaluated maximal oxygen uptake (VO2max) and time to exhaustion by cardiorespiratory test performed on treadmill, and the percentage of body fat was measured by skinfold. The evaluations were performed before the beginning of the training (baseline), 4, 8, and 12 weeks after the beginning of the training, and also 4 weeks after the detraining. The percentage of change in MVC test for the PBMT/sMF+PBMT/sMF group was of 30% compared to the Placebo+Placebo group at 16th week, and in the 1RM tests, this percentage was of 30% on leg extension and of 47% on leg press compared to the Placebo+Placebo group at 16th week. Regarding the time until exhaustion and VO2max, the percentage of change was statistically superior in the PBMT/sMF+PBMT/sMF group at 16th week compared to that in the Placebo+Placebo group. Finally, the percentage of change in body fat at the 16th week improved in the PBMT/sMF+PBMT/sMF group compared to the Placebo+Placebo group. In the present study, the use of PBMT/sMF was able to potentiate the effects of strength training, as well as aerobic training. In addition, it reduced the losses caused by a period without training.